Matricaria Recutita Extract (Chamomile) to reduce Candida Albicans and Entrobacter Cloacae biofilms: in vitro study - PEQUENO,Maitê Alves (2018)
ABSTRACT Objective: This research study aimed at evaluating the inhibitory activity of Matricaria recutira (chamomile) hydroalcoholic extract on Candida albicans and Enterobacter cloacae biofilms. Methods: C. albicans and E. cloacae biofilms with thirty-hour formation were submitted, for five minutes, to 100, 200 and 300 mg / mL of M. recutita hydroalcoholic extract, chlorhexidine digluconate 0.12% (Periogard® - inhibition control) or sterile distilled water (growth control). Subsequently, they were washed and divided into two groups to determine the microbial viability: G/UFC - counting of colony forming units (cfu) in agar and G/DNA - quantification of viable DNA with violet crystal dye by spectrophotometry. Results: M. recutita extract at 300 mg/mL reduced significantly (p <0.01) the E. cloacae cfu/mL number in biofilm with results similar to chlorhexidine 0.12%, while extracts at 100 and 200 mg/mL did not have the same effectiveness. The amount of E. cloacae viable DNA was reduced (p <0.05) in all the M. recutita extract concentrations and chlorhexidine. There was no significant difference (p = 0.565) in the cfu/mL number or in the amount of viable DNA (p = 0.8094) in C. albicans biofilm when compared to untreated biofilm (control) or, even, between the extracts when compared to each other or to chlorhexidine 0.12%. Conclusion: 300 mg/mL M. recutita extract reduced significantly the E. cloacae biofilm but not the C. albicans, both with a similar result to chlorhexidine 0.12% (Periogar®).